Analysis of Experiential Function on The Jakarta Post about Opinion Academy Robot and AI: A New Economic Era - Rohanna Sinambela; Agnes Gau Densia Bulu; Shinta Grace Adinda Sirait; Herman Herman; Endang Fatmawati; Arwin Tannuary (Jurnal Scientia, 2023)
This research is aimed to look for the elements of Experiential function that is used on Jakarta Post about opinion academic Robot and AI: A new Economic Era. Therefore, the researcher will analyze the component of experiential function on Jakarta Post about opinion academic Robot and AI: A new Economic Era. In this research, the researcher used qualitative method by analyzing the text of the newspaper. This research finds the transitivity system as a unit of experience in three elements namely participants, process and circumstances. The part of the participants namely actor, senser, sayer, carrier, token, possessor, behaver with calculate is 58 participants. The highest participant is actor (47%). The second process namely material, behavior, mental, verbal, relational, existential with calculate is 67 processes, and the highest process is material (50%). The third is circumstance namely manner, extent (temporal), accompaniment, role, location (temporal & spatial), cause, contingency with calculates 39. The highest circumstance is contingency (33%)